-34=2x+6(x-3)

Simple and best practice solution for -34=2x+6(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -34=2x+6(x-3) equation:



-34=2x+6(x-3)
We move all terms to the left:
-34-(2x+6(x-3))=0
We calculate terms in parentheses: -(2x+6(x-3)), so:
2x+6(x-3)
We multiply parentheses
2x+6x-18
We add all the numbers together, and all the variables
8x-18
Back to the equation:
-(8x-18)
We get rid of parentheses
-8x+18-34=0
We add all the numbers together, and all the variables
-8x-16=0
We move all terms containing x to the left, all other terms to the right
-8x=16
x=16/-8
x=-2

See similar equations:

| |z-8|+6=9 | | -2d=-4−2d | | 2x=x-1=0 | | 3(w-4)+5(2w+1)-(13w+9)=0 | | v−10=-3v+10 | | 3+4t=5t+9 | | 4/3=2/3t7/3 | | -8y+20=-4(y+1) | | 54b^2+90b-36=0 | | 96=3(k+11) | | y+2.6=8.71 | | 8x-20=12×+4 | | 97=9w+7 | | c-11/(1/7)=1 | | (3x+5)=(2x | | 45+12h=123 | | 5=15-2k | | 18*3+y=23 | | (3m+2)/2+6m=8.5 | | u/4+3=6 | | 7x+10=9×+40 | | 4x^{2}-52x+169=121 | | x+0.1x=3.50 | | 4(2x-5)=7(2x+4) | | x+1/2x+1/3x=17 | | X=(3x+5) | | x+1/2x+1/3=17 | | 4((3m+2)/(2+6m))=34 | | 7/2(5x=2) | | 5x+7=6x+20 | | 5x+7=6x+205x+7=6x+20 | | 4((3m+2)/2+6m)=34 |

Equations solver categories